FRI0667 The recall survey: can ultrasound affects clinicians' decisions about changing treatment in ra?. (15th June 2017) - Epis, O; Macchioni, P; Sedie, A Delle; Canzoni, M; Filippucci, E; Iagnocco, A; Tropea, S; Bonali, CF
Abstract : Background: In Rheumatoid Arthritis (RA) treatment response is assessed using standard clinical disease activity measure. However ultrasound (US) is able to show subclinical synovitis in patients (pts) with RA who are in clinical remission (CR); further studies are still required to delineate the impact of US findings in the management of RA pts in daily clinical practice. Objectives: to investigate the influence of US on the clinicians' treatment choices in pts with RA. Methods: in 2015 an educational event (RECALL Survey) focused on the added value of US in RA pts was held in 22 rheumatology centers in Italy.In every center, the local rheumatologists provided RA pts to be examined by US. Pts signed an informed consent and a brief history of them was collected by the local rheumatologists (previous and current therapy, DAS28, HAQ score). Bilateral US examinations of wrists, metacarpophalangeal (MCP) and metatarsophalangeal (MTP) joints were performed by rheumatologists expert in US, to assess synovitis (joint effusion, synovial proliferation, and power Doppler (PD) signal), and bone erosions, using a Logiq E R7, General Electrics, with a 4.2–13 MHz linear probe. All US findings were scored using a 4 degree semiquantitative scoring system. Results: 465 pts were evaluated. Clinicians, after US evaluations, changed therapy in 23.7% of pts, did not change therapy in 35.5% of pts.In general changes of therapy tended to be made by clinicians when joint effusion or power Doppler signal were present (table 1 –2). The presence of erosion did not influence the clinicians' decisions. Conclusions: Ultrasound may be an useful tool in daily rheumatologic practice to help clinicians make decisions about how to treat patients with RA. US results, especially joint effusion and Power Doppler signal, may influence the choice of clinicians to modify a patient's treatment regime. Disclosure of Interest: None declared